2021
DOI: 10.3390/microorganisms9050931
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological Features Shape the Distribution of Prophages and CRISPR in Sulfate Reducing Prokaryotes

Abstract: Sulfate reducing prokaryotes (SRP) are a phylogenetically and physiologically diverse group of microorganisms that use sulfate as an electron acceptor. SRP have long been recognized as key players of the carbon and sulfur cycles, and more recently, they have been identified to play a relevant role as part of syntrophic and symbiotic relations and the human microbiome. Despite their environmental relevance, there is a poor understanding about the prevalence of prophages and CRISPR arrays and how their distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Polytomies were collapsed using the function multi2di in ape [55]. Copiotroph and oligotroph classification was according to Stone et al 2023 for species 2-10, and suspected classifications (indicated with questions marks) are from [58] (species 2), [59] (species 11), and [60] (species 12-13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polytomies were collapsed using the function multi2di in ape [55]. Copiotroph and oligotroph classification was according to Stone et al 2023 for species 2-10, and suspected classifications (indicated with questions marks) are from [58] (species 2), [59] (species 11), and [60] (species 12-13).…”
Section: Methodsmentioning
confidence: 99%
“…Values in (A) are the scores of p-PC1 and values in (B) are the scores of p-PC2 (Fig. 2A).Copiotroph and oligotroph classification was according to[58] (species 1),[5] (species 2-10),[59] (species 11), and[60] (species 12-13) (questions marks indicate suspected classifications).…”
mentioning
confidence: 99%
“…Some phylogenetically diverse functional groups have a high prevalence of CRISPR/Cas. For instance, a comparative analysis of 91 sulfate-reducing prokaryote (SRP) genomes revealed the existence of CRISPR/Cas systems in as many as 78% of taxa [ 53 ]. This frequency is remarkably higher than in other reported prokaryotes.…”
Section: Huge Inventory Of Crispr/cas In the Oceanmentioning
confidence: 99%
“…Prophages are increasingly recognized as an important component in the complex interplay between host, pathogen and environment associated with CF (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%